Landscape analysis in time and space through the supervised classification of the municipality of Belém in the period 2008 to 2020 (Research, Society and Development, 2023)
Due to centuries of formation and development, the history of Belém is confused with the history of Pará itself. However, there were factors that influenced the crisis, causing the territory of Belen to gradually urbanize. The present work aimed to spatially analyze the landscape of the municipality of Belém regarding the classes of forest, vegetation, urban area, exposed soil and water, using knowledge about remote sensing and geoprocessing techniques through supervised classification applied to images from the years 2008 , 2020 by the QGIS software in version 3.16.7, to demonstrate the change in the territory of Belen in this 10-year interval. With this method it was possible to obtain good and effective results as the geotechnology tools such as ARCGIS both to perform the visual classification and the supervised classification and the minimum distance method obtained satisfactory results, it was possible to notice in this study that there was a decrease of 0.53 % in the year 2008 to 0.48% in the year 2020 and a growth in relation to vegetation from 0.25% to 0.32%, while the urban area had a growth from 0.13% in 2008 to 0.19 % in 2020 and obtained a decrease in relation to the exposed soil from 0.09% to 0.08%. With this, we can emphasize that the use of geotechnology significantly contributes to studies on the dynamics of natural phenomena and helps in understanding changes in a territory over time. In this way, these digital tools allow the construction of models for anticipating changes and minimizing impacts.